2011
DOI: 10.1007/s00210-011-0710-2
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotection by marine-derived compound, 11-dehydrosinulariolide, in an in vitro Parkinson’s model: a promising candidate for the treatment of Parkinson’s disease

Abstract: Parkinson's disease (PD) is a neurodegenerative disease characterized by tremor, rigidity, bradykinesia, and gait impairment. So far, very few pharmacological agents have been isolated or developed that effectively inhibit the progression of PD. However, several studies have demonstrated that inflammatory processes play critical roles in PD. Therefore, anti-inflammatory agents may suppress disease progression in PD. 11-Dehydrosinulariolide was isolated from cultured soft corals. The anti-inflammatory effect of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 47 publications
2
49
1
Order By: Relevance
“…In our previous work, we only investigated 11-de protection of SH-SY5Y cells against 6-OHDA-induced damage via the PI3K/Akt pathway in an in vitro model [8]. However, our present study reveals that 11-de protects SH-SY5Y cell against 6-OHDA-induced cell damage via a DJ-1 modulated pathway that includes both the Akt/Nrf2 pathway and the Akt/CREB pathway.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…In our previous work, we only investigated 11-de protection of SH-SY5Y cells against 6-OHDA-induced damage via the PI3K/Akt pathway in an in vitro model [8]. However, our present study reveals that 11-de protects SH-SY5Y cell against 6-OHDA-induced cell damage via a DJ-1 modulated pathway that includes both the Akt/Nrf2 pathway and the Akt/CREB pathway.…”
Section: Discussionmentioning
confidence: 69%
“…In addition, Su et al (2012) revealed that 11-de induces apoptosis of A2058 cells through the dysregulation of mitochondria and the endoplasmic reticulum stress pathway [7]. Moreover, our previous study also indicated that 11-de protects neuronal-like cells against 6-OHDA-induced cytotoxicity through the PI3K/Akt pathway [8]. Liu et al (2011) used two-dimensional gel electrophoresis (2-DE) to show that 11-de upregulated DJ-1 protein expression [6].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, pre-treatment with 11-dehydrosinulariolide (10 nM) also inhibited the down-regulation of phospho-Akt protein expression induced by 6-OHDA, as well as inhibited 6-OHDA-induced caspase-3/7 activation and 6-OHDA-induced translocation of NF-κB to the nucleus. 11-Dehydrosinulariolide (10 nM) inhibited the down-regulation of p-ERK induced by 6-OHDA [176]. The PI3K–Akt and ERK (p42/p44 mitogen-activated protein kinase) pathways are important factors in neuronal cell survival.…”
Section: Protective Effect Of Marine Drugs Using Cell Models For Nmentioning
confidence: 99%
“…The PI3K–Akt and ERK (p42/p44 mitogen-activated protein kinase) pathways are important factors in neuronal cell survival. Their activation was suggested to have neuroprotective effects in PD [176]. AKT, a Ser/Thr protein kinase, regulates a variety of cellular processes, including cell survival, proliferation, protein translation and metabolism [177].…”
Section: Protective Effect Of Marine Drugs Using Cell Models For Nmentioning
confidence: 99%
See 1 more Smart Citation